Alfred Verdross – A Visionary of Contemporary Doctrine and Practice of International Law - Koeck, Heribert Franz Koeck (Studia Iuridica Toruniensia, 2011)
<!--[if gte mso 9]> <![endif]--> Prof. Witkowski who was kind enough to present us to you in this honouring way referred to the proclamation of the state of emergency and of martial law that took place in Poland on the 13th of December 1981, exactly 29 years ago. Let me tell you that we have always admired the courage of those who have made Poland a beacon of civil resistance against an oppressive system within the communist block eight years before those communist regimes began to falter and fi nally broke down. This courage of the Polish people was certainly an important fact which contributed – together with other facts and persons, not to forget the Polish pope – to the dawn of freedom and democracy in those parts of Europe which so long suff ered from oppression. We shall always keep all these persons and the sacrifi ces they made in high respect. <!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->